Joint effect of multiple air pollutants on daily emergency department visits in Chengdu, China. (February 2020) - Zhu, Yue; Wang, Yanyan; Xu, Huan; Luo, Bin; Zhang, Wei; Guo, Bing; Chen, Shiqi; Zhao, Xing; Li, Weimin
Abstract: Existing studies have typically investigated only the association between single pollutants and health outcomes. However, in the real world, people are exposed to multiple air pollutants simultaneously. The effect of air pollutants on emergency department (ED) visits has not been previously studied in the Sichuan Basin, which is one of the most polluted areas. We collected nonaccidental, respiratory and cardiovascular daily ED visits and daily concentrations of PM2.5, PMc, CO, SO2, NO2 and O3 in Chengdu, China, from 2014 to 2016. A weighted variable for the combination of multiple air pollutants was constructed to assess the joint adverse health effects. Each air pollutant was assigned a health-related weight, which indicated the pollutant's relative contribution to the joint effect. The effects on specific subpopulations (males and females; 15–65 years old and >65 years old) were also examined. With an increase of 10 μg/m 3 of the combined multiple air pollutants, the daily ED visits for nonaccidental, respiratory and cardiovascular causes increased by 0.96% (95% CI: 0.51%–1.39%), 1.19% (95% CI: 0.53%, 1.85%) and 4.36% (95% CI: 1.06%, 7.76%) at lag 1, respectively. Males presented more pronounced effects, except for cardiovascular disease, than females. Elderly individuals were found to be more sensitive than young individuals. For nonaccidental and respiratory diseases, the contributions of particulate matter (PM) were dominant among the air pollutants, whereas cardiovascular disease was mainly affected by gaseous air pollutants. The combination of multiple air pollutants was significantly associated with ED visits in the Sichuan Basin, China. The joint effect of the combination of multiple air pollutants was highest for cardiovascular disease at lag 1. The relative contributions of individual pollutants varied by disease and subpopulation. These findings suggest that under different pollution scenarios, preventive strategies should target those with different diseases and different subpopulations. Graphical abstract: Image 1 Highlights: The joint effects on emergency department visits were significant. The contributions of pollutants varied by disease and subpopulation. Particulate matter had dominant effect on nonaccidental and respiratory diseases. Gaseous pollutants had important effect on cardiovascular disease. Abstract : The joint effect of multiple air pollutants on ED visits was highest for cardiovascular disease at lag 1, and the contributions of pollutants varied by disease and subpopulation.